Superdisintegrant Properties of Coprocessed Ipomoea batatas Starch, Microcrystalline Cellulose and Lactose Monohydrate in Folic Acid Oro-Dispersible Tablet Formulations - Oduola, A. R.; Okpanachi, G. O.; Ohwoavworhua, F. O. , (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The superdisintegrant properties of co–processed Ipomoea batatas starch (IBS), microcrystalline cellulose (MCC) and lactose monohydrate (LMH) in folic acid oro – dispersible tablet formulations in comparison with sodium starch glycolate (SSG) and crospovidone (CROSPOV) were investigated. IBS was extracted by standard method of extraction, and its physicochemical properties were evaluated and compared with co – processed excipient (CPE) and physical mixture of excipients (PME). Folic acid oro – dispersible tablets were prepared by direct compression using CPE, PME, SSG and CROSPOV at concentrations of 2.5, 5.0, 7.5, 10.0 and 12.5 % and evaluated for tablet properties. Excipient – excipient and drug – excipient interactions using Fourier Transform Infrared (FTIR) were also investigated. Co – processing with MCC and LMH improved moisture sorption capacity (from 24 to 39 %) and flow properties, as revealed in the values of angle of repose (from 25.2 to 29.08o) and flow rate (from 3.22 to 5.2 g/s). Oro – dispersible tablets that met the standard specifications for crushing strength (4 – 7 Kgf) and disintegration time (< 3 min) were produced. FTIR analyses revealed no interactions between excipients or between excipients and drugs. The results obtained show that in folic acid oro – dispersible tablets prepared by direct compression method, co – processing IBS with MCC and LMH converts it to a superdisintegrant that is directly compressible with high bond strength.